2009
DOI: 10.2174/156720509788486644
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vascular Factors in Late-Onset Sporadic Alzheimers Disease. Genetic and Molecular Aspects

Abstract: Alzheimer's disease (AD) is a late-onset progressive neurodegenerative disorder which results in the irreversible loss of cortical neurons, particularly in the associative neocortex and hippocampus. AD is the most common form of dementia in the elderly. Apart from the neuronal loss, the pathological hallmarks are extracellular senile plaques, containing the peptide beta-amyloid (Abeta), and neurofibrillary tangles. The Abeta cascade hypothesis remains the main pathogenetic model, as suggested by familiar AD, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 180 publications
(275 reference statements)
0
39
0
1
Order By: Relevance
“…It is well known that patients with stroke and cerebral infarction are at risk of AD (Rocchi et al 2009).…”
Section: Hypoxiamentioning
confidence: 99%
“…It is well known that patients with stroke and cerebral infarction are at risk of AD (Rocchi et al 2009).…”
Section: Hypoxiamentioning
confidence: 99%
“…88 Based on the above epidemiological, clinical, and structural neuroimaging findings, it has been proposed recently that AD and VaD actually represent two extremes of a dementia spectrum ranging from patients with pure VaD to patients with pure AD, with a majority of patients having contributions from both neuropathological pathways. 53,74,89,90 Figure 1 (adapted from Viswanathan et al 90 ) illustrates the concept of a spectrum ranging from pure AD to pure VaD. Such lines of evidence have also provided support to a more ambitious ''vascular hypothesis'' for AD, which proposes that the neuropathological changes that characterize AD would originate primarily from microvascular abnormalities.…”
Section: Cardiovascular Risk Factors and Cognitive Declinementioning
confidence: 97%
“…Today, it is believed to be associated with excessive extracellular beta-amyloid and intracellular hyperphosphorylated tau protein accumulation eventually leading to the loss of cholinergic neurons and relative glutamate excess. (Rocchi et al, 2009) VAD, accounting for 10-20% of all dementia patients, is characterized by a stepwise deteriorating course and a patchy distribution of neurologic deficits (affecting some functions and not others) caused by cerebrovascular disease. It is not a single disease, but rather a group of syndromes relating to different vascular mechanisms.…”
Section: Dementia Syndromesmentioning
confidence: 99%
“…Other possible genes include VLDL-R, LRP, NOS3, CST3, OLR1, MTHFR, PON1 and VEGF, but many of the related studies have shown conflicting results. (Rocchi et al, 2009) Some strokes are clinically detected, while others go undetected. Silent strokes are, also, associated with higher age, elevated blood pressure and AF.…”
Section: Af Stroke and Dementiamentioning
confidence: 99%